Anion exchange influence on the electrochemomechanical properties of polyaniline - Lizarraga, Leonardo (2007)
The anion influence on the volume changes of polyaniline (PANI) thick films (∼200 μm) during redox switching was studied using voltammetric experiments with simultaneous microscopical observation. The area occupied by the polymer film in the microscope images was measured and used to compute the film volume and its variations. It is found that the electrolyte anion has a definite influence on the film volume changes. When a film equilibrated with perchloric acid is transferred to sulphuric acid, fully reduced and relaxed and afterwards subject to voltammetric cycling, a net volume increase is observed, spanning several potential cycles until a stationary profile is reached. This change is not reversed when the film is transferred back to perchloric medium, and in this electrolyte the response shows a faster evolution. Exchanges with hydrochloric acid show behaviour more similar to HClO4. IR measurements show that anion exchange is complete before the voltammetric cycling is started, indicating that anion ingress/exchange alone is not the only cause for PANI volume changes. The results are interpreted in terms of polymer backbone conformational changes and polymer/anion interactions.